Total impact evaluation of transportation systems - Rohács, József; Rohács, Dániel (Transport, 2020)
Impact assessment, in general, includes the environmental safety and security considerations, and cost/cost-benefit analysis of the used sources. As usual, the impact is evaluated at two levels: (1) impact during operation (usage) related to a chosen operational unit (e.g., running distance [km], operational time [h] or calendar time [h]), (2) the life-cycle (project life-cycle) impact. The environmental impact is characterized by the chemical and noise emissions. Safety and security are estimated by risks. Costs are calculated based on the required financial support and caused losses. All these calculations are related to the individual vehicles or vehicles with average behaviours. The investigation of sustainability impact requires a wider evaluation and approach, for example, by also including production and recycling beside the operational aspects. This paper generalizes the impact analysis. At first, it considers all types of impacts including the direct (e.g., accidents) and indirect long-term effects (e.g., health problems caused by emissions). All the impacts are expressed as costs. The defined Sustainable Transportation Performance Index (STPI) is the Total Life-Cycle Cost (TLCC) related to the unit of transport work. As such, it combines the life-cycle emissions evaluation and transport costing methods. It contains the total operational and total impact costs. The proposed approach introduces three new specific features in the impact analysis: (1) the impact is evaluated on the transportation system level, (2) the impact is estimated as the total value (including all the related sub-systems and elements, like vehicles, transport infrastructure, transport flow control, etc.), (3) proposes a unique index to describe the total impact. The paper describes the general equations and the developed methodology for the estimation of the total impact and analyses its applicability. The preliminary results demonstrate the applicability of the defined index and its evaluation methodology. It also shows the limitations of traditional cost models. Further test results and wider application of the methodology will be provided in a series of follow up papers by the research team.